Dostoevskij in Italia e nel mondo (ENTHYMEMA, 2011)
From the 13th to the 20th of June, 2010, many notable Dostoevsky’s scholars have met in Naples for the XIVth International Dostoevsky Symposium Dostoevsky. Philosophical Mind, Writer’s Eye, a conference organized by the International Dostoevsky Society.